2022
DOI: 10.1111/are.16138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein level on growth, histology and digestive enzyme activities of ornamental fish Ancistrus cirrhosus

Abstract: Regardless of the developmental stage of the cultured organism, proper nutritional care is essential. A significant number of aquacultural species rely on protein as their main energy source and protein feeds sold in the ornamental market are formulated with widely varying protein inclusion levels. As Ancistrus cirrhosus is one of the most popular ornamental fish species, this study aimed to determine the effects of different protein levels on growth, digestive enzyme activities and liver and intestinal histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…In the present study, digestive enzyme activities showed significant alterations with different protein levels and culture temperatures. Protease activities increased with increasing levels of CP and temperature, which can be explained by the fact that increasing protein levels require more proteases to breakdown proteins (Şahin & Gürkan, 2022), and higher temperatures accelerate protease activities (Mazumder et al, 2018). In the current study, an increase in CP levels decreased amylase activities, which is due to the decreasing carbohydrate content in diets.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, digestive enzyme activities showed significant alterations with different protein levels and culture temperatures. Protease activities increased with increasing levels of CP and temperature, which can be explained by the fact that increasing protein levels require more proteases to breakdown proteins (Şahin & Gürkan, 2022), and higher temperatures accelerate protease activities (Mazumder et al, 2018). In the current study, an increase in CP levels decreased amylase activities, which is due to the decreasing carbohydrate content in diets.…”
Section: Discussionmentioning
confidence: 99%